Attitudes and policies toward Turgut Ozal issue Kurdish 1984-1993 - قبس ناطق محمد هدى هادي احمد (College of Education for Women, 2019)
After receipt of military commanders power in 1980, they were determined to solve the Kurdish question by force, just like their predecessors in resolving such issues, and the situation became worse when the Kurdish resistance in a more organized than previous years and behind the Party (PKK) . After the mass support of the Kurdish widespread party get involved most of the Kurdish youth in the party organization of the (PKK), prompting Turkish President then to make decisions and take immediate action firm against the party, but the Kurdish issue began Tthlhal when he arrived at the helm of President Turgut Ozal in 1989, he worked on the development of the areas inhabited by the Kurds, specifically the Southeast Anatolia and the events of demographic changes And reduce the cultural differences between the eastern and southern sections eastern and western sections of the country through the employment possibilities and capabilities enjoyed by the province of the same natural resources and river basins, and the hands of the worker, then the followers of the new policy is more flexible and openness towards the Kurds.